STRATEGI PEMASARAN DAN PENGEMBANGAN TEPUNG CASSAVA PADA AGROINDUSTRI UD. NULA ABADI DI KABUPATEN BONDOWOSO - Achmad Budi Santoso; Joni Murti Mulyo Aji (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
Cassava flour is one of the derivative products obtained from cassava processing. Cassava flour is different from tapioca because of soaking process and has higher nutritional value. This research is aimed to seek to analyze: 1) Channels and marketing efficiency of cassava flour, 2) Revenue and cost efficiency of cassava flour production and 3) Strategy recommendation for developing cassava flour production and marketing. The research area is determined purposively method with the consideration that UD. Nula Abadi is a new agroindustry with innovative products that are still not widely known by people in Bondowoso Regency. The sample of the producer is determined using purposive sampling and snowball sampling especially for the marketing agency. Data were collected by interview, observation, and documentation. Data analysis used in this research include marketing margin, share and efficiency to answer the first problem and analysis of income as well as R/C ratio to answer the second problem. The analysis of marketing channels and SWOT is done descriptively to answer the third problem. The results showed that 1) marketing channel of cassava flour on UD. Nula Abadi consists of 3 marketing channels and the most efficient marketing is that in channel II (Manufacturer - Large trader - Consumer household / agroindustry). 2) Total revenue of cassava flour Rp. 6.250.000,00 with total production costs of Rp. 3,525,458,33, so that the amount of income is Rp. 2,724,541,67. The value of production cost efficiency (R/C ratio) obtained is 1,17. 3) The competitive relative position of cassava flour agroindustry is located in the field of White Area or potentially strong field, meaning that the agroindustry can use its competence to exploit the prospective opportunity.